Nanofibrous Membrane with Encapsulated Glucose Oxidase for Self-Sustained Antimicrobial Applications - Fernaldy Leonarta; Cheng-Kang Lee (Membranes, 2021)
Polyvinyl alcohol (PVA) nanofibrous membrane, consisting of separately encapsulated glucose oxidase (GOx) and glucose (Glu) nanofibers, was prepared via simultaneously electrospinning PVA/GOx and PVA/Glu dopes. The as-prepared pristine membrane could self-sustainably generate hydrogen peroxide (H2O2) only in contact with an aqueous solution. The H2O2 production level was well maintained even after storing the dry membrane at room temperature for 7 days. Cross-linking the membrane via reaction with glutaraldehyde (GA) vapor could not only prevent the nanofibrous membrane from dissolving in water but also prolonged the release of H2O2. The sustained release of H2O2 from the membrane achieved antimicrobial capability equivalent to that of 1% H2O2 against both Escherichia coli and Staphylococcus aureus. Gram(+) S. aureus cells were more susceptible to H2O2 than Gram(−) E. coli and >99% of S. aureus were killed after 1 h incubation with the membrane. Pristine and GA-crosslinked nanofibrous membrane with in situ production of H2O2 were self-sterilized in which no microorganism contamination on the membrane could be detected after 2 weeks incubation on an agar plate. The GOx/Glu membrane may find potential application as versatile antimicrobial materials in the field of biomedicine, in the food and health industries, and especially challenges related to wound healing in diabetic patients.